Peningkatan Fokus dan Pemahaman Budaya Lokal Melalui Kegiatan Kontekstual Membawa Kue Tradisional Betawi Siswa Kelas 1 SD Kemala Bhayangkari 1 - Isriyani, Nofi; Dwinata, Anggara (IJPSE Indonesian Journal of Primary Science Education, 2026)
This study aims to improve students' learning focus and understanding of local culture through contextual activities of bringing traditional Betawi cakes. The background of this study is the low concentration and interest of students in learning about their local culture. The research method used is Classroom Action Research (CAR) which was implemented in two cycles. The subjects of the study were 36 first-grade students of Kemala Bhayangkari 1 Elementary School, consisting of 16 male students and 20 female students. The research approach used was a qualitative study with a case study research design. Data collection techniques used observation, interviews, and documentation, while data analysis was carried out descriptively qualitatively. The results of the study showed an increase in students' learning focus and understanding of local culture after participating in the activity of bringing traditional Betawi cakes. Students became more active, enthusiastic, and able to explain the cultural meaning of the cakes they brought. Thus, contextual learning based on local culture has proven effective in improving the quality of student learning processes and outcomes in elementary schools.